WTO negotiations on agriculture and developing countries - Hoda, Anwarul; Gulati, Ashok (International Food Policy Research Institute, 2008)
In this study, our aim is to develop the strategy that would be in the best interest of developing countries to adopt in the multilateral trade negotiations on agriculture in the Doha Round. Before reaching our conclusions we delve deeply into the evolution of rules and disciplines on agricultural trade policies in the General Agreement on Tariffs and Trade (GATT) after its establishment in 1947 and analyze the complex provisions of the WTO Agreement on Agriculture. We undertake an examination of the implementation of that agreement by the two major industrialized economies—the United States and the European Community—and India and also look at how some of the other WTO members have fared in discharging their obligations under that agreement. We give a detailed account of the negotiations until the breakdown of talks in the last week of July 2006, discussing the issues that remained outstanding at that time. Finally, we outline the elements of the approach that would be the most beneficial for the developing countries to adopt in future negotiations. While we have put greater focus on India, we believe that the approach outlined for it is equally valid for many developing countries not belonging to the Organisation for Economic Co-operation and Development. Like India, many of these developing countries are low-cost producers of farm products and earn substantial amounts of foreign exchange from exporting these products. They too have large proportions of the population dependent on agriculture for their livelihood and use domestic support and export subsidies on a far lower scale than the industrialized countries. An important part of the study is an examination of India's competitiveness in agricultural products.